Expertise revisited, Part I—Interactional expertise. (December 2015) - Collins, Harry; Evans, Robert
Abstract: In Part I of this two part paper we try to set out the 'essence' of the notion of interactional expertise by starting with its origins. In Part II we will look at the notion of contributory expertise. The exercise has been triggered by recent discussion of these concepts in this journal by Plaisance and Kennedy and by Goddiksen.